An Online Career Intervention for Promoting Chinese High School Students’ Career Readiness - Chen, Shi; Chen, Huaruo; Ling, Hairong; Gu, Xueying (Frontiers in Psychology, 2022)
To assist Chinese high school students in improving their career readiness and tackling career decision-making difficulties, we designed a synchronous online career intervention based on the Cognitive Information Processing (CIP) theory during the Covid-19 pandemic. The online career intervention consisted of a series of career courses to develop high school students’ knowledge and skills in career planning, career assessments for exploring their vocational interests and academic self-concept, and a database providing basic information about university majors. To evaluate the intervention’s effectiveness, 957 10th grade students were recruited in the study, 601 participants (girls=227, boys=324) were randomly assigned to the experimental group (online career intervention), and 356 (girls=159, boys=197) participants were randomly assigned to the control group (no any career interventions). All participants completed a pre- and post-intervention assessment of their career maturity, vocational identity and career decision-making difficulties. Results indicated that the online intervention significantly increased high school students’ career readiness and reduced their career decision-making difficulties. The practical implications of this research for online career interventions directed at Chinese high school students are also discussed.